PENGARUH BIAYA KUALITAS TERHADAP MINIMALISASI PRODUK RUSAKPADA PRODUKHOME INDUSTRI PEMBUATAN KUE DONAT - Rina Milyati Yuniastuti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2020)
This study aims to determine whether there is a simultaneous influence on prevention costs and valuation costs. Research with objects in the home industry makes Kinanti donuts. From the results of the F test there is a significant effect between the cost of prevention and the cost of evaluating the damaged product on Kinanti donuts. And also to minimize the damaged product on the donut is done by knowing how to fry. Because the frying process has to be careful by paying attention to the flame and the oil that has been hot for a long time makes the donut cake burn easily. It is also expected that the fire should be more stable or smaller after the hot oil